2016
DOI: 10.1021/acs.chemrestox.5b00524
|View full text |Cite
|
Sign up to set email alerts
|

P450 3A-Catalyzed O-Dealkylation of Lapatinib Induces Mitochondrial Stress and Activates Nrf2

Abstract: Lapatinib (LAP), an oral tyrosine kinase inhibitor for the treatment of metastatic breast cancer, has been associated with idiosyncractic hepatotoxicity. Recent investigations have implicated the importance of P450 3A4/5 enzymes in the formation of an electrophilic quinone imine (LAPQI) metabolite generated through further oxidation of O-dealkylated lapatinib (OD-LAP). In the current study, hepatic stress was observed via mitochondrial impairment. OD-LAP caused a time- and concentration-dependent decrease in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 34 publications
1
29
2
Order By: Relevance
“…Contribution of CYP3A4 and CYP3A5 to Lapatinib Bioactivation administration to Nrf2-knockout and control mice led to elevated liver transaminases, which levels returned to baseline after repeat dosing in control mice but continued to rise in Nrf2 knockout mice, indicating that Nrf2 may be involved in cellular defense against lapatinib-induced hepatotoxicity (Eno et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Contribution of CYP3A4 and CYP3A5 to Lapatinib Bioactivation administration to Nrf2-knockout and control mice led to elevated liver transaminases, which levels returned to baseline after repeat dosing in control mice but continued to rise in Nrf2 knockout mice, indicating that Nrf2 may be involved in cellular defense against lapatinib-induced hepatotoxicity (Eno et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…CYP3A4 induction by dexamethasone and rifampin potentiated lapatinib-induced cytotoxicity, which was correlated with increased formation of LAP-OH and reactive quinoneimine-cysteine conjugates (Hardy et al, 2014). More recently, Cameron and colleagues showed that O-dealkylated lapatinib induced mitochondrial stress and activation of the oxidative stress responsive transcription factor nuclear factor erythroid 2-related factor 2 (Nrf2) in HepG2 cells (Eno et al, 2016). Lapatinib Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eno et al examined the cellular effects of lapatinib vs its O -dealkylated metabolite in HepG2 cells [62]. Mitochondrial respiration, as measured by oxygen consumption rate, was monitored using a Seahorse XF24 analyzer.…”
Section: Downstream Toxicity Mechanisms Of Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
“…The results of this study demonstrated that O -dealkylated lapatinib caused mitochondrial dysfunction in a time- and concentration-dependent manner. Treatment of HepG2 cells with 30 μM O -dealkylated lapatinib for 24 h significantly reduced basal and maximal oxygen consumption rate compared to untreated cells [62]. The parent drug lapatinib did not significantly alter mitochondrial respiration in HepG2 cells at the concentration tested (10 μM lapatinib).…”
Section: Downstream Toxicity Mechanisms Of Tyrosine Kinase Inhibitorsmentioning
confidence: 99%